The Role of Banking Digitalization in Improving Financial Performance - Harmelani, Indah; Cahyaningtyas, Susi Retna (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to fills the gap in the existing literature and provides valuable information for banking practitioners and policy makers in understanding how digitalization affects the financial performance of banks in Indonesia. This study uses a comparative research method (difference test) with a quantitative approach. The data used are secondary data obtained from the banking Annual Reports of the last three years when the bank was still operating as a conventional bank, namely 2018 - 2020 with the last three years after the bank transformed into a fully digital bank, namely 2021 - 2023. The results of the study show that ROA, ROE, BOPO do not show significant differences after digitalization. However, NPL shows a significant difference after undergoing digitalization.